2005
DOI: 10.4012/dmj.24.642
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acidic Primers on Bonding Three Magnetic Steel Alloys with Tri-n-butylborane Initiated Methacrylic Resin

Abstract: The purpose of this study was to evaluate the effect of acidic primers on bonding magnetic steel alloys.Three alloys (XM27, 447J1, and AUM20) were primed with one of the following materials: Acryl Bond, Estenia Opaque Primer, Eye Sight Opaque Primer, M. L. Primer, or Super-Bond liquid. The specimens were bonded with a tri-n-butylborane initiated resin, and bond strength was determined both before and after thermocycling in water. Unprimed specimen was considered as the control.Average bond strength varied from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 16 publications
5
10
3
Order By: Relevance
“…This implied that MDP was superior to carboxylic monomer, such as 4-META and MAC-10, in terms of bonding characteristics. This result well agreed with other studies although the studies were carried out about titanium and other base metal alloys [32,33,44,45].…”
Section: Discussionsupporting
confidence: 92%
“…This implied that MDP was superior to carboxylic monomer, such as 4-META and MAC-10, in terms of bonding characteristics. This result well agreed with other studies although the studies were carried out about titanium and other base metal alloys [32,33,44,45].…”
Section: Discussionsupporting
confidence: 92%
“…Between the two phosphate monomers, i.e., hydrophobic MDP and hydrophilic methacrylate phosphate (MP), the former demonstrated better bond durability to base metal alloys than the latter 19,26) .…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that carboxylic monomers rather than a silane monomer were effective for bonding alumina. Similarly, other studies demonstrated the effectiveness of MDP monomer in bonding dental base metal alloys and base metals [19][20][21][24][25][26] . Both base metal alloys and alumina are usually covered with a metal oxide layer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fixation strengths would depend on both the adhesive strength and the mechanical retention between the magnetic assembly and the fixation materials 29,30) . In the present study, application of a conventional metal primer and Super-Bond was examined to investigate the effectiveness of the adhesive strength.…”
Section: Discussionmentioning
confidence: 99%